Industrial trans-fat: a cause of concern for Indian population - Kumar, Rakesh; Vignesh K., Nawin Jai; ., Anbuselvi; ., Anudharani; ., Angeeth (International Journal Of Community Medicine And Public Health, 2022)
The trans-fats are a form of unsaturated fatty acids which contain one or more unconjugated double bonds in the trans-configuration. Trans-fat is found in natural sources such as dairy products and meat but the quantity of trans-fatty acid in natural sources is meagre. Most commonly they are found in industrial food products like bakery products, cookies and snacks. Several studies have identified increased industrial trans-fat consumption as harmful to human health. The major effects are on the cardiovascular system and central nervous system. To reduce the trans-fatty acid consumption, the global and national organizations have proposed various approach and strategies like WHO ‘Replace’ action plan strategy, implementation of trade policies and guidelines, work-site intervention strategies, improvements in hydrogenation technology, labeling of food products, behavioural change communication for population. Trans-fatty acid consumption is a modifiable risk factor. Planning and implementation of government policies and guidelines for reduction of trans-fatty acid levels in food product can have a significant impact. But behavioural change among general population is the key to reduce trans-fatty acid consumption.